2009
DOI: 10.1063/1.3074786
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic force microscopy of alternating magnetic field gradient by frequency modulation of tip oscillation

Abstract: A new magnetic force microscopy (MFM) technique for measuring alternating magnetic field (ac magnetic field) was proposed by using frequency modulation (FM) phenomenon of tip oscillation. We detected a narrowband FM phenomenon in the tip oscillation of a high-coercivity MFM tip by applying an ac magnetic field to the tip by using a metal-in-gap (MIG) type ring head. In the experiment, the MFM tip was driven at a constant frequency fc near the resonant frequency of the cantilever by a piezoelectric element, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…And the frequency of fc±2fm is dominating when coercivity of the magnetic component of the tip is smaller than the AC magnetic field. This is because, the spectrum intensity at fc±fm is proportional to the gradient of magnetic field component which is perpendicular to the sample surface 9) , and this indicates that direction of tip magnetization does not change when the fc±fm is dominant. In Fig.7 (a), the modulated frequency with highest peak of the spectra was fc±fm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…And the frequency of fc±2fm is dominating when coercivity of the magnetic component of the tip is smaller than the AC magnetic field. This is because, the spectrum intensity at fc±fm is proportional to the gradient of magnetic field component which is perpendicular to the sample surface 9) , and this indicates that direction of tip magnetization does not change when the fc±fm is dominant. In Fig.7 (a), the modulated frequency with highest peak of the spectra was fc±fm.…”
Section: Resultsmentioning
confidence: 99%
“…The lift height was 10 nm. The amplitude and phase information of the alternating force between the sample and the tip was extracted by using a lock-in amplifier where the input signal was the frequency demodulated signal of cantilever oscillation from a phase-locked loop (PLL) circuit and reference signal was the frequency signal of fm from signal generator 8), 9) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 This method uses the frequency modulation ͑FM͒ of a cantilever oscillation by applying ac magnetic field to a mechanically oscillated tip. We found that ac magnetic field caused the FM of a cantilever oscillation when ac magnetic field does not oscillated the cantilever by itself in the case that the frequency of ac magnetic field is far from the resonant frequency of the cantilever.…”
Section: Introductionmentioning
confidence: 99%
“…We mentioned this type of microscopy as frequency modulated-magnetic force microscopy (FM-MFM). 5 In this study, we proposed a stroboscopic analysis method for AC magnetic fields by varying the phase of the measured in-phase and quadrature signals via a signal processing technique. The stroboscopic imaging of a timevariable AC magnetic field for a perpendicular magnetic recording head, caused by the rotation of the magnetisation around the main pole using a head-current driving magnetic field, was demonstrated.…”
mentioning
confidence: 99%